Formation of language and communicative competence of PhD students in classes of Ukrainian Scientific Language - Chueshkova , O. (Problems of Engineer-Pedagogical Education, 2023)
The article deals with the analysis of the most common language errors in scientific works of young researchers and suggests effective mechanisms for the formation of language and communicative competence of PhD students within the "Ukrainian Scientific Language" course. The term "scientific language" is considered; it is stated that mastering Ukrainian for scientific purposes is an important prerequisite to perfect scientific writing and successful presentation of research results. At the same time, it is noted that modern scientific works often contain a breach of language norms (scientists have even initiated a special area of research – "linguistics of errors", or "error studies", "deviatology"). Language competence is interpreted as knowledge of the norms of modern literary language and ability to practically apply them in accordance with the types of linguistic norms; orthoepic, accentual, lexical, word-building, morphological, syntactic, orthographic, punctuation and stylistic language competences are singled out. Based on the fact that language competence is a component of communicative one, the unified term is proposed – language and communicative competence, which is defined as a set of knowledge about communication in different conditions and ability to apply this knowledge in practice, which will allow students to freely present and discuss research results as well as to decently reflect them in scientific publications. An overview of language norms breach in scientific writing of young researchers, as well as a system of exercises and tasks aimed at developing sustainable skills in this area is proposed. It is believed that philological knowledge acquired by PhD students when taking the course will help to improve general language culture of both the future scientific elite and society as a whole.